Risk assessment of Kermanshah gas storage tanks by energy trace and barrier analysis (2014) - M. Ghanbari Kakavandi; F. Rajati; H. Ashtarian; SY. Hosseini (The Journal of Qazvin University of Medical Sciences, 2016)
Background: Despite the cost and millions loss of life due to industrial accidents, often are preventable through risk assessment methods and control measures. Objective: To assess the safety of gas storage tanks in Kermanshah oil refinery by Energy Trace and Barrier Analysis (ETBA). Methods: This case-descriptive study was conducted in gas storage tanks of Kermanshah oil refinery. Energy checklist was used for identification of energy types. Energy flows were tracked and then, management and administrative procedures, and personal protective equipment were considered as safeguard. Exposed and vulnerable targets are also specified. Preliminary levels of risks were determined by combination of severity and likelihood. After suggestion of corrective action for unacceptable risks, risk assessment took place again. Identified risks were expressed using descriptive statistics such as frequency and percentage. Findings: Overall, 74 risks and 121 dangerous energies were identified. Of these, 25 risks were unacceptable, 46 were low risk, and 3 were acceptable risk with revised. Frequency of risks related to electric power was 20, and followed by risk of displacement- pressure-volume, potential and chemical energies, with frequencies of 13, 12 and 9, respectively. Conclusion: Given the environmental and protection conditions of the tanks, in addition, the high percentage of some of the damaging risks in this industry, use of appropriate control measures to prevention the event of future disasters will be inevitable.